Use of Online Social Networking Sites by College Students and its Implications for Marketing: A Case Study in Tripura - Dash, Ajit Kumar (Indian Journal of Marketing, 2011)
This paper is an attempt to study the use of social networking sites by the college students (UG and PG) and how the use affects the demographic profile and educational attainment level. To achieve the objectives, a primary survey was conducted among 300 students. We found that, both male and female students are members of different social networking sites. Orkut, My space and E-mail are popular among students. There is a significant difference between UG and PG level in case of use of SNS for study and research only, but there is no significant difference between graduation level and use of SNS for activities like E-mail, instant messaging, getting news, playing games, shopping, keeping in touch with others and membership of online communities. Since more than half of the total number of users communicate with each other, and share their views relating to satisfaction and dissatisfaction relating to a product, therefore, it is necessary to ensure product quality before advertising a product online.